2013
DOI: 10.1111/jonm.12123
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of hospitals and nurse‐reported care quality, work environment, burnout and leaving intentions

Abstract: Structural characteristics of hospitals and nurse-reported care quality, work environment, burnout and leaving intentions Aim To investigate whether hospital characteristics not readily susceptible to change (i.e. hospital size, university status, and geographic location) are associated with specific self-reported nurse outcomes. Background Research often focuses on factors within hospitals (e.g. work environment), which are susceptible to change, rather than on structural factors in their own right. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
5
33
5
Order By: Relevance
“…This collaborative nursing workforce study involving 16 countries worldwide included a nurse survey, an optional patient survey (not carried out in Sweden) and an organizational survey (www.rn4cast.eu/en/ index.php) and has been described in depth elsewhere (Aiken et al, 2014;Lindqvist et al, 2015;Sermeus et al, 2011). The primary aim of RN4CAST was to introduce innovative workforce forecasting methods addressing characteristics of both nursing staff and work environment with attention given to effects on patient care (Sermeus et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This collaborative nursing workforce study involving 16 countries worldwide included a nurse survey, an optional patient survey (not carried out in Sweden) and an organizational survey (www.rn4cast.eu/en/ index.php) and has been described in depth elsewhere (Aiken et al, 2014;Lindqvist et al, 2015;Sermeus et al, 2011). The primary aim of RN4CAST was to introduce innovative workforce forecasting methods addressing characteristics of both nursing staff and work environment with attention given to effects on patient care (Sermeus et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…among people less familiar with their coworkers. 23 Furthermore, the association of nursing burnout with average number of daily admissions suggests that the nursing workload associated with a new admission may be underappreciated, creating the potential for relative understaffing. 24 Although there is a paucity of published data on the subject, 25 new admissions may necessitate more rapid and efficient decisionmaking, increased intellectual effort to address diagnostic uncertainty, and emotional expenditure related to engaging and orienting new family members.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, emergency rooms and palliative care units are the least investigated sites probably due to difficulties in research operationalization (14,41,57,102) , although a small concentration of studies on OBS in intensive care nurses can be found (19,22,(39)(40)(92)(93) . Still, the need for further investigations on OBS in professionals from acute care (59,62) and psychiatric ward units (57,86) is clear, given that these are places which in theory present greater risks in relation to the syndrome due to the type of work performed and the attended patients.…”
Section: Obs Among Nursing Professionals In Health Facilitiesmentioning
confidence: 99%
“…Studies rely on samples ranging from 11 to 11,000 participants, and because there is no standard for measuring the syndrome, it is not possible to conduct a more categorical assessment of the results. However, by analyzing the mean scores of some studies, in most cases it can be noticed that nursing professionals manifest low-moderate EE, low DS and moderate PA (2)(3)17,19,23,(27)(28)30,34,36,(49)(50)(51)(52)(53)(54)57,(59)(60)(62)(63)(64)(73)(74)(75)(76)(77)(78)(79)(81)(82)(83)(84)(85)(86)91,(93)(94)101,105) . Nursing technicians and assistants have higher levels of the syndrome compared to nurses, although this difference is small (10,13,50,91) .…”
Section: Obs Among Nursing Professionals In Health Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation